(3) \( \frac{\left(2 \times 10^{2}\right)^{3}\left(6 \times 10^{-2}\right)^{2}}{\left(2 \times 10^{-2}\right)\left(3 \times 10^{4}\right)^{2}}= \)
Real Tutor Solution
Answer
Solution
Reviewed and approved by the UpStudy tutoring team
Bonus Knowledge
To solve the expression, we can first simplify each component step by step. 1. Calculate each term: - \( \left(2 \times 10^{2}\right)^{3} = 2^{3} \times (10^{2})^{3} = 8 \times 10^{6} \) - \( \left(6 \times 10^{-2}\right)^{2} = 6^{2} \times (10^{-2})^{2} = 36 \times 10^{-4} \) - \( \left(2 \times 10^{-2}\right) = 2 \times 10^{-2} \) - \( \left(3 \times 10^{4}\right)^{2} = 3^{2} \times (10^{4})^{2} = 9 \times 10^{8} \) 2. Putting it all together: \[ \frac{\left(2 \times 10^{2}\right)^{3}\left(6 \times 10^{-2}\right)^{2}}{\left(2 \times 10^{-2}\right)\left(3 \times 10^{4}\right)^{2}} = \frac{(8 \times 10^{6})(36 \times 10^{-4})}{(2 \times 10^{-2})(9 \times 10^{8})} \] 3. Multiply the numerator: \[ 8 \times 36 = 288 \quad \text{and} \quad 10^{6} \times 10^{-4} = 10^{2} \] So, the numerator becomes \( 288 \times 10^{2} \). 4. Multiply the denominator: \[ 2 \times 9 = 18 \quad \text{and} \quad 10^{-2} \times 10^{8} = 10^{6} \] So, the denominator becomes \( 18 \times 10^{6} \). 5. Now we have the expression: \[ \frac{288 \times 10^{2}}{18 \times 10^{6}} = \frac{288}{18} \times \frac{10^{2}}{10^{6}} \] 6. Calculate \( \frac{288}{18} = 16 \) and \( \frac{10^{2}}{10^{6}} = 10^{-4} \). 7. Therefore, the result is: \[ 16 \times 10^{-4} = 1.6 \times 10^{-3} \] The final answer is: \[ \boxed{1.6 \times 10^{-3}} \]